Golden Arches of Success: Enhancing Customer Relationship Management at McDonald's, Wide Angle, Ahmedabad - Dharmik Chalplot; Smilee Jagetiya; Jignesh Vidani (International Journal of Educational and Life Sciences, 2024)
Customer Relationship Management (CRM) is crucial in the retail business, especially in the highly competitive fast-food sector. This research examines the customer relationship management (CRM) strategies used by McDonald's, Wide Angle in Ahmedabad. The objective is to get insights into their methods of managing customer relationships and improving corporate performance. The goals include evaluating current CRM strategies, identifying strengths and areas for improvement, and offering practical suggestions to increase CRM performance. The study used a qualitative research methodology, including semi-structured interviews with branch managers to get in-depth understanding of McDonald's customer relationship management (CRM) activities. The key results include McDonald's tactics for managing data, techniques for segmenting customers, avenues for contact, and programmes for fostering loyalty. The investigation demonstrates a significant focus on customisation, the use of technology, and the incorporation of client feedback methods. The strengths that have been highlighted include the implementation of comprehensive communication strategies and the successful implementation of loyalty programmes. On the other hand, the problems that need to be addressed are the integration of feedback into practical and effective initiatives.